Adsorbent and its manufacturing method

JP7641142B2Active Publication Date: 2025-03-06FUJITA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021038614
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2025-03-06
Estimated Expiration
2041-03-10

AI Technical Summary

Benefits of technology

【0008】 本発明の実施形態により、長期間に亘って河川や湖沼、海などの水域の水質改善に対する有効性を示し、かつ安全性の高い吸着材、およびその製造方法を提供することができる。また、植物の育成に対して効果を有する肥料を低コストで製造することが可能となる。さらに、大気中の二酸化炭素を炭素という形で地中に貯留し、温室効果の抑制に寄与することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641142000002
    Figure 0007641142000002
  • Figure 0007641142000003
    Figure 0007641142000003
  • Figure 0007641142000004
    Figure 0007641142000004
Patent Text Reader

Abstract

To provide an adsorbent which can be used for water quality improvement, has low ignitability, and can be safely treated, and a method for producing the same.SOLUTION: An adsorbent has a core containing a porous carbide, a binder and iron powder, and a coating layer covering at least a part of the core. The adsorbent can have a pellet shape with a length to a diameter of 0.5 or more and 5 or less and the diameter of 1 mm or more and 20 mm or less. The coating layer may include a material selected from sodium silicate, potassium silicate, a silicon oxide, a resin, iron powder, gypsum and cement.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to an adsorbent and a method for producing the same. [Background technology]

[0002] It is known that an adsorbent in which iron is supported on a porous carbide having carbon prepared from biomass as a basic material can adsorb phosphate ions derived from phosphoric acid, and can therefore be used to improve the water quality in water areas such as rivers, lakes, and oceans. In addition, since the adsorbent with phosphate ions adsorbed can also be used as fertilizer, it is possible to effectively utilize the carbon dioxide fixed by plants and store the carbon dioxide in the soil by spreading the adsorbent after phosphate adsorption. Therefore, adsorbents obtained from biomass play a central role in carbon storage for fixing greenhouse gases in the atmosphere (see Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-75706 A [Non-patent literature]

[0004] [Non-Patent Document 1] Akira Shibata, "Simple carbonization of biomass and carbon storage vegetables for regional development" Journal of High Temperature Society, March 2011, Vol. 37, No. 2, pp. 37-42 Summary of the Invention [Problem to be solved by the invention]

[0005] One of the embodiments of the present invention has an object to provide an adsorbent and a manufacturing method thereof. Alternatively, one of the embodiments of the present invention has an object to provide an adsorbent that can be used for water quality improvement, has low ignition properties, and can be handled safely, and a manufacturing method thereof. Alternatively, one of the embodiments of the present invention has an object to provide an adsorbent that can be used for water quality improvement and can maintain its shape in water for a long period of time, and a manufacturing method thereof. Alternatively, one of the embodiments of the present invention has an object to provide a system for storing carbon through fixation of carbon dioxide in the atmosphere. [Means for solving the problem]

[0006] One embodiment of the present invention is an adsorbent having a core including porous carbide, a binder, and iron powder, and a coating layer covering at least a portion of the core.

[0007] One embodiment of the present invention is a method for making an adsorbent material, the method including mixing a porous carbide with a binder and an iron powder to form a mixture, and forming a coating layer over at least a portion of the mixture. Effect of the Invention

[0008] According to the embodiment of the present invention, it is possible to provide an adsorbent that is effective for improving the water quality of water bodies such as rivers, lakes, and oceans over a long period of time and is highly safe, and a manufacturing method thereof. It is also possible to manufacture fertilizers that are effective for plant growth at low cost. Furthermore, it is possible to store carbon dioxide in the atmosphere in the form of carbon underground, thereby contributing to the suppression of the greenhouse effect. [Brief description of the drawings]

[0009] [Figure 1] 1A and 1B are schematic perspective and end views of an adsorbent according to one embodiment of the present invention; [Diagram 2] 1 is a flowchart showing a method for producing an adsorbent according to one embodiment of the present invention. [Diagram 3]FIG. 1 is a conceptual diagram showing a carbon dioxide storage system according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, each embodiment of the present invention will be described with reference to the drawings, etc. However, the present invention can be embodied in various forms without departing from the gist of the present invention, and should not be construed as being limited to the description of the embodiments exemplified below.

[0011] In order to make the explanation clearer, the drawings may show the width, thickness, shape, etc. of each part diagrammatically compared to the actual embodiment, but these are merely examples and are not intended to limit the interpretation of the present invention.

[0012] In this specification and claims, the expression "a structure is exposed from another structure" means an embodiment in which a part of a structure is not covered by another structure, and includes an embodiment in which the part not covered by the other structure is covered by yet another structure.

[0013] First Embodiment In this embodiment, an adsorbent 100 according to one embodiment of the present invention and a method for producing the same will be described. 1. Adsorbent 1-1.Structure Fig. 1(A) shows a schematic perspective view of adsorbent 100, and Fig. 1(B) shows a schematic view of an end surface perpendicular to the length direction. As shown in these figures, adsorbent 100 basically comprises a core 102 and a coating layer 104 covering core 102.

[0014] The shape of the adsorbent 100 is arbitrary, and may be a plate or sphere, or may be in the form of a so-called pellet as shown in Fig. 1(A). In the case of a pellet shape, the shape of the adsorbent 100 may be a cylinder as shown in Fig. 1(B), or may be a cylinder (prism) with polygonal end faces, such as an elliptical cylinder, triangular prism, quadrangular prism, pentagonal prism, or hexagonal prism (not shown). In addition, the adsorbent 100 may have the shape of a cylinder, elliptical cylinder, or square prism with a portion missing.

[0015] When the adsorbent 100 is cylindrical, its diameter D may be 1 mm or more and 20 mm or less, 2 mm or more and 11 mm or less, or 3 mm or more and 8 mm or less. 2 More than 300mm 2 The aspect ratio of the adsorbent 100, i.e., the ratio of the length L to the diameter D (L / D), is also arbitrary and can be, for example, from 0.5 to 5. Specifically, the length L can be from 1 mm to 20 mm, from 3 mm to 15 mm, or from 6 mm to 12 mm.

[0016] The core 102 is a component for realizing the functions of the adsorbent 100, and has a porous carbide as a basic skeleton. On the other hand, the coating layer 104 is a component that imparts physical strength to the core 102 and contributes to improving the safety of the adsorbent 100 by reducing ignition tendency. The coating layer 104 may be provided so as to cover the entire surface of the core 102, or may be provided so as to cover a part of the surface of the core 102 and expose the other part of the surface of the core 102 from the coating layer 104, as shown in FIG. 1(C).

[0017] 1-2. Core The core 102 includes porous carbide, iron (zero-valent iron) supported on its surface and in its pores, and a binder. The supported iron causes phosphoric acid and its ions present in the water to become iron phosphate, which is then adsorbed to the porous carbide. This allows the adsorbent 100 to be used as an adsorbent for effectively improving the water quality of bodies of water such as rivers, lakes, and oceans. The adsorbent 100 may include an iron compound, and may further include a compound of a metal selected from alkali metals and alkaline earth metals. The adsorbent 100 may further include water as another component.

[0018] (1) Porous carbide A porous charcoal is a charcoal produced by using an organic material as a raw material and heating and carbonizing the organic material under conditions of low oxygen concentration. An example of the organic material is biomass. Examples of porous charcoal derived from biomass include charcoal, bamboo charcoal, white charcoal, black charcoal, sawdust charcoal, coconut shell charcoal, and rice husk charcoal. As described later, by using biomass as a raw material for a porous charcoal, a system for storing carbon dioxide in the atmosphere can be constructed, and ions of alkali metals and alkaline earth metals that act as reaction sites for preventing the adsorbent 100 from collapsing in water can be provided.

[0019] Carbonization is carried out by heating the organic matter in an inert gas atmosphere such as nitrogen gas or argon gas, an oxygen-free atmosphere, a low-oxygen atmosphere, a reducing atmosphere, or a reduced pressure atmosphere. 2 Pa or more 10 5 Low vacuum state below 10 Pa -1 Pa or more 10 2 Medium vacuum state below 10 Pa -5 Pa or more 10 -1 High vacuum state of 10 Pa or less -5 The carbonization can be carried out in an ultra-high vacuum state of 0.01 Pa or less. When the carbonization is carried out in a low-oxygen atmosphere, the oxygen concentration can be set to 0.01% to 3%, or 0.1% to 2%. The heating temperature in the carbonization can be 400°C to 1200°C, 500°C to 1100°C, 600°C to 1000°C, or 600°C to 900°C. The heating time can be 10 minutes to 10 days, or 10 minutes to 5 hours.

[0020] Carbonization is carried out using an internal combustion or external heat carbonization furnace. Examples of carbonization furnaces include batch-type closed charcoal kilns, continuous rotary kilns, rocking carbonization furnaces, and screw furnaces. Carbonization of biomass generates dry distillation gas, and produces porous charcoal with pores of various shapes and sizes, which are a complex mixture of pores due to the structure of the biomass and pores formed by the desorption of dry distillation gas. Dry distillation gas mainly contains combustible or reducing gases such as hydrogen, carbon monoxide, and alkanes such as methane, propane, and butane. Dry distillation gas is extracted at high temperatures (700°C to 1300°C), so its thermal energy and combustibility can be used as an energy source for power generation, hot water supply, etc.

[0021] Here, biomass refers to a type of organic matter, that is, a substance derived from a living organism and its metabolites. For example, materials derived from wood are examples of biomass. Specifically, examples include plank-shaped or column-shaped wood, thinning materials, pruning waste, construction waste wood, powdered sawdust, particle boats, and other wooden molded products. There are no restrictions on the type of wood, and it can be cedar, cypress, or bamboo. Other examples of biomass include agricultural waste such as rice husks, bagasse, corn cobs and leaves, and agricultural by-products such as straw, wheat straw, and hay. Other examples include plants that are the raw material for fibers, such as hemp, flax, cotton, sisal, abaca, and palm hair. Other examples include algae such as seaweed. Other examples include food waste and silage obtained from animal manure.

[0022] The size and shape of the porous carbide are not particularly limited, but the average particle size may be 1 μm to 50 mm or 1 μm to 1 mm. By having the average particle size in this range, the porous carbide and the iron powder can be mixed uniformly in the mixing and kneading process described later.

[0023] Due to the pores formed inside, porous carbides have a large specific surface area. 2 / g or more 900m 2 / g or less, 100m 2 / g or more 800m2 / g or less, or 150m 2 / g or more 400m 2 The specific surface area is measured by a mercury intrusion method or a gas adsorption method such as the BJH method or the HK method.

[0024] (2) Iron and iron compounds As described later, iron is mixed with porous carbide as iron powder and supported. There is no restriction on the shape of the iron powder. For example, iron powder with an average circularity of 50 to 100, 70 to 95, or 80 to 90 may be used. The average circularity is one of the parameters that represent the shape of each iron particle contained in the iron powder, and is an average value obtained by analyzing an image obtained by observing the iron powder under a microscope, determining the circularity of a plurality of iron particles. As the circularity, for example, a value obtained by dividing the perimeter of a circle having an area equal to the area of ​​the projection surface of each iron particle in the microscope image by the perimeter of the projection surface of each iron particle in the microscope image can be used. Alternatively, a value obtained by dividing the area of ​​the projection surface by the area of ​​a circle inscribed in the projection surface may be used as the circularity.

[0025] There is no restriction on the average particle size of the iron powder, and it may be, for example, an iron powder having an average particle size in the range of 20 μm to 500 μm or 50 μm to 200 μm. Here, the average particle size of the iron powder is a value obtained by averaging the particle sizes of a plurality of iron particles obtained by analyzing an image obtained by observing the iron powder under a microscope. The particle size of each iron particle may be, for example, the diameter of a circle inscribed in the projection surface of each iron particle in the microscope image or the length of one side of a square.

[0026] The iron powder may contain trace amounts of other elements, such as carbon, oxygen, sulfur, phosphorus, manganese, silicon, vanadium, copper, titanium, etc. Thus, the purity of the iron powder may be 90.0% to 99.9% or 95.0% to 99.0%.

[0027] In addition, a part of the iron powder may be supported on the porous carbide in an oxidized state, that is, as an iron compound. Examples of the iron compound include iron oxide and iron hydroxide. The iron contained in the iron compound may be present in a divalent, trivalent, or mixed valence state in which divalent and trivalent valences are mixed. Therefore, when the iron compound is iron hydroxide, it may be ferrous hydroxide or ferric hydroxide. When the iron compound is iron oxide, it may be wustite (FeO), hematite or maghemite (Fe2O3), or magnetite (Fe3O4).

[0028] (3) Binder The binder is used to efficiently disperse the porous carbide and iron powder in the kneading process described later, and to integrate the iron or iron compounds with the porous carbide. There is no restriction on the type of binder, and organic and / or inorganic binders can be used. Examples of organic binders include one or more selected from molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified form thereof, pulp waste liquor, lignin sulfonate, carboxymethyl cellulose, hydroxypropyl methyl cellulose, sodium alginate, phenolic resin, and tar pitch. Among them, molasses is inexpensive, contains few harmful components, and contains many solid components, so that the use of molasses makes it easy to form the adsorbent 100. Examples of inorganic binders include cement, ground granulated blast furnace slag, fly ash, gypsum (calcium sulfate), calcined gypsum obtained by heating and dehydrating gypsum, and sodium silicate.

[0029] (4) Compounds of alkali metals and alkaline earth metals Compounds of metals selected from alkali metals and alkaline earth metals include halides, oxides, hydroxides, sulfates, nitrates, carbonates, and hydrogen carbonates of sodium, potassium, lithium, cesium, magnesium, and calcium. These compounds may be added during the production of the adsorbent 100, but when biomass is used as the raw material for the porous charcoal, they may be compounds of alkali metals or alkaline earth metals contained in the biomass.

[0030] When the compound of an alkali metal or alkaline earth metal is a carbonate or hydrogen carbonate, it may be, for example, a carbonate or hydrogen carbonate obtained by reacting a hydroxide, chloride, oxide, sulfate, or nitrate of an alkali metal or alkaline earth metal contained in or added to a porous carbide with carbon dioxide (hereinafter, referred to as carbonation).

[0031] (5) Composition ratio The composition ratio of the above-mentioned configurations can be adjusted appropriately. For example, the content of the porous carbide in the adsorbent 100 may be adjusted to a range of 20% by mass to 80% by mass, 40% by mass to 80% by mass, or 60% by mass to 80% by mass. The content of the iron powder may be adjusted to a range of 5% by mass to 35% by mass, 5% by mass to 25% by mass, or 5% by mass to 20% by mass. The content of the binder may be adjusted to a range of 5% by mass to 50% by mass, 15% by mass to 50% by mass, or 20% by mass to 50% by mass. The sum of the contents of the alkali metal and the alkaline earth metal may be adjusted to a range of 1% by mass to 30% by mass, 1% by mass to 15% by mass, or 1% by mass to 10% by mass.

[0032] Alternatively, the carbon content in the adsorbent 100 may be adjusted from a range of 10% by mass to 80% by mass. The iron content (i.e., elemental iron including zero-valent iron and iron ions) in the adsorbent 100 may be adjusted from a range of 5% by mass to 35% by mass. In addition, the sum of the alkali metal and alkaline earth metal contents may be adjusted from a range of 1% by mass to 30% by mass.

[0033] In measuring the content of the porous carbide in the adsorbent 100, first, the carbon content of the porous carbide in the raw material stage is measured. For example, a method conforming to JIS H1617, JIS Z2615, and ASTM E1941 may be adopted using a combustion and infrared absorption method. Specifically, the porous carbide in the raw material stage is burned in an oxygen stream in a combustion furnace to generate carbon dioxide. The generated carbon dioxide is introduced into an infrared analyzer using oxygen gas, and its absorption is measured with a detector to determine the concentration of carbon dioxide. From this carbon dioxide concentration, the mass of carbon in the porous carbide in the raw material stage is quantified as the mass of the porous carbide. After that, the content of the porous carbide may be determined from the mass of the porous carbide in the raw material stage and other raw materials such as the binder, iron powder, and water mixed with the porous carbide. The content of the iron powder and binder may also be calculated from the masses of the iron powder, binder, porous carbide, water, etc. used in the manufacturing process of the adsorbent 100.

[0034] The above-mentioned method does not take into account the reaction rate of the hydroxide, chloride, oxide, sulfate, or nitrate of an alkali metal or alkaline earth metal with carbon dioxide, or the change in mass of the adsorbent 100 due to this reaction. It also does not take into account the generation of iron compounds due to the oxidation of iron in the manufacturing process. However, since the change in mass due to these reactions is within a negligible range, it can be said that the reliability of the measurement results obtained by the above-mentioned method is sufficiently high.

[0035] The sum of the contents of the metals selected from the alkali metals and the alkaline earth metals can be measured by applying, for example, inductively coupled plasma optical emission spectroscopy (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS) to the adsorbent 100. In ICP-OES, argon plasma is used as an emission source, and a mist of the solution sample is introduced into the plasma to disperse the spectra specific to the alkali metals and the alkaline earth metals, so that the alkali metals and the alkaline earth metals can be quantified from the measured wavelength and emission intensity. In ICP-MS, argon plasma is used as an ion source to ionize the elements contained in the sample, and the ions are separated and detected based on their mass-to-charge ratio. The elements can be identified from the mass-to-charge ratio of the detected ions, and the alkali metals and the alkaline earth metals can be quantified by counting the detected ions.

[0036] On the other hand, the carbon content in the adsorbent 100 can be obtained by applying the above-mentioned combustion / infrared absorption method to the adsorbent 100. The carbon content in the adsorbent 100 is the content of carbon derived mainly from the porous carbide, the binder, and the carbonates and hydrogen carbonates of metals selected from alkali metals and alkaline earth metals. The iron content and the sum of the alkali metal and alkaline earth metal contents can also be measured by applying ICP-OES or ICP-MS to the adsorbent 100.

[0037] 1-3.Coating layer The coating layer 104 covers the whole or part of the core 102. The coating layer 104 includes an inorganic compound such as sodium silicate, calcium silicate, or silicon oxide, or a resin. The inorganic compound may be iron powder, gypsum (calcium sulfate), or cement. The resin may be an acrylic resin, an epoxy resin, polylactic acid, polystyrene, polyethylene, or polyester. Preferably, an inorganic compound with a low load on the natural environment is used. The coating layer 104 may have a thickness of, for example, 10 μm to 1 mm, 50 μm to 500 μm, or 100 μm to 300 μm.

[0038] The coating layer 104 may be composed of a single layer, or may be composed of a plurality of layers containing different materials laminated together.

[0039] When the raw material of the coating layer 104 is liquid, the coating layer 104 may be formed by applying the raw material of the coating layer 104 to the core 102 by spray coating, dip coating, or the like. Examples of the liquid raw material include an aqueous solution of sodium silicate or potassium silicate, and an alcohol solution of a tetraalkoxysilane such as tetramethoxysilane or tetraethoxysilane. When a tetraalkoxysilane is used as a raw material, the tetraalkoxysilane is quickly hydrolyzed by water in the air and condensed to form a coating of silicon oxide. When the coating layer 104 contains a resin, the coating layer 104 can be formed by applying a monomer or oligomer as a raw material, and then polymerizing or crosslinking it by heating or irradiating it with light. Alternatively, the coating layer 104 may be formed by applying a solution of a polymer as a raw material, and then evaporating the solvent to form the coating layer 104.

[0040] When the raw material of the coating layer 104 is a solid, the coating layer 104 may be formed by spraying water or alcohol onto the core 102 and then contacting the raw material of the coating layer 104 in that state.

[0041] Covering the surface of the core 102 with the coating layer 104 imparts physical strength to the adsorbent 100. Therefore, even if the adsorbent 100 is placed in water for a long period of time to improve the water quality of bodies of water such as rivers, lakes, and oceans, the adsorbent 100 is prevented from being eroded by water and collapsing, and can function as an adsorbent for a long period of time.

[0042] Furthermore, by forming coating layer 104 within the above-mentioned thickness range, the water to be treated can diffuse through coating layer 104 and come into contact with core 102. Furthermore, by partially covering the surface of core 102 so that a part of the surface is exposed, the water to be treated can come into direct contact with core 102. Therefore, even if coating layer 104 is provided, the function of core 102 as an adsorbent is not impaired.

[0043] The phosphate adsorption ability of the adsorbent 100 can be determined, for example, by a batch test. The batch test is a method of calculating the amount of adsorbed phosphate from the difference between the phosphate concentration of a solution containing the adsorbed phosphate and the phosphate concentration of the supernatant after the phosphate is adsorbed. The phosphate concentration can be determined, for example, by using the molybdenum blue method or the ammonium vanadomolybdate absorbance method. In the former method, a potassium peroxodisulfate solution is added to a certain amount of sample taken and heated, and a mixed solution of ammonium molybdate and dipotassium bis[(+)-tartrate]diantimonate(III) trihydrate is added to generate molybdophosphoric acid. An L-ascorbic acid solution is added to this molybdophosphoric acid to generate molybdenum blue (hydrated mixed-valence oxide of molybdenum). The amount of water-soluble phosphate is quantified by measuring the absorption of molybdenum blue (for example, absorption at 880 nm) using an ultraviolet-visible spectrophotometer. In the latter method, a certain amount of sample is heated with nitric acid (1+1) to hydrolyze non-orthophosphate to orthophosphate ion. Ammonium vanadate(V), hexaammonium heptamolybdate, and nitric acid are then added to produce phosphovanadomolybdate. Phosphate is quantified by measuring the absorption of phosphovanadomolybdate (e.g., at 420 nm) using a UV-Vis spectrophotometer.

[0044] 2. Manufacturing method The following describes one example of a method for producing the adsorbent 100. A flow chart showing the method for producing the adsorbent 100 is shown in FIG.

[0045] 2-1.Mixing and kneading As shown in FIG. 2, first, the raw materials, porous carbide, binder, and iron (iron powder), are mixed and then kneaded (mixed). As described above, it is preferable to use carbide obtained by carbonizing biomass as the porous carbide. The amounts of the porous carbide, binder, and iron powder are appropriately adjusted so that the composition ratio falls within the above-mentioned range. The porous carbide may be crushed or classified in advance to adjust its particle size. Since the particle size of the porous carbide is often larger than that of the iron powder, the porous carbide may be crushed so that the particle size is approximately the same as that of the iron powder.

[0046] When mixing or kneading, water is added to the porous carbide, binder, and iron as necessary. By adding water, it is possible to prevent dust generation and to mix the porous carbide and iron powder more uniformly.

[0047] A kneader can be used to mix and knead these raw materials. As the kneader, for example, a single-screw kneader, a twin-screw kneader, a mixing roll, a kneader, or a Banbury mixer can be used. A kneader having both mixing and kneading functions can also be used. In this case, the porous carbide, iron powder, and binder are charged into the kneader, and then mixed and kneaded. Alternatively, mixing and kneading can be performed continuously. For example, the porous carbide and iron powder are charged into the kneader and mixed, and then the binder is charged into the kneader and kneaded. The binder may be added all at once, intermittently, or continuously. By adding the binder after mixing the porous carbide and iron powder and kneading, it is possible to prevent the porous carbide and iron powder from agglomerating and suppress foaming.

[0048] The kneading temperature can be set arbitrarily, for example, from 0° C. to 50° C., or from 10° C. to 40° C. The kneading time can also be set appropriately in consideration of the mixing ratio and amount of the raw materials, the type of binder, the capacity of the kneader, and the like, and can be set within the range of, for example, from 1 second to 1 hour, from 1 minute to 30 minutes, or from 1 minute to 15 minutes.

[0049] Through the above steps, a paste-like mixture of the porous carbide, binder, and iron powder can be obtained as the core 102. Note that in this step, a portion of the iron powder may be oxidized, and as a result, the mixture contains compounds containing divalent and / or trivalent iron (Fe(II), Fe(III)). As described above, examples of iron compounds include iron hydroxide and iron oxide. Furthermore, during mixing and kneading, a compound of an alkali metal and / or an alkaline earth metal may be added.

[0050] 2-2. Granulation As an optional step, the mixture may be granulated and formed into a certain shape, such as pellets. The mixture may be formed using a granulator. Examples of the granulator include a compression granulator, an extrusion granulator, a roll granulator, a blade granulator, a melt granulator, or a spray granulator.

[0051] When using an extrusion type granulator, a paste-like mixture molded into a predetermined shape is extruded from a die attached to the granulator. The extruded mixture is cut into a predetermined length and molded into pellets with the extrusion direction being the height direction. The length of the mixture (pellet length L) can be adjusted by adjusting the extrusion speed and cutting speed of the mixture in the extrusion type granulator (rotation speed of the cutter in the case of a rotary cutting method). In addition, the diameter of the mixture (diameter D when the end face shape is circular) can be adjusted by adjusting the opening diameter of the die. Therefore, by using an extrusion type granulator, a mixture in the form of pellets (for example, approximately cylindrical) with a controlled size can be obtained. The size of the pellets is adjusted to have a diameter D and length L within the above-mentioned range, for example.

[0052] Through the above steps, the core 102 is formed.

[0053] 2-3. Formation of coating layer Next, the coating layer 104 is formed on the surface of the core 102. Specifically, the liquid raw material of the coating layer 104 described above is applied to the surface of the core 102 by spray coating or dip coating. Then, the solvent contained in the raw material can be distilled off. In the case of spray coating, for example, the raw material can be sprayed while the core 102 is rotated on a pan-type granulator. The thickness of the coating layer 104 can be appropriately adjusted by the concentration of the raw material, the number of applications, etc.

[0054] When the raw material of the coating layer 104 is solid, for example, pellet-shaped core 102 is placed in a pan-type granulator, and water or alcohol is sprayed onto the core 102 while rotating it. The raw material is then placed in the core 102 to adhere the raw material of the coating layer 104 to the surface of the core 102. The water or alcohol used to bond the core 102 and the raw material is then distilled off to form the coating layer 104.

[0055] Through the above steps, the adsorbent 100 is produced.

[0056] 2-4. Carbon dioxide treatment As an optional configuration, carbon dioxide treatment may be performed. Specifically, the material is treated with a gas containing carbon dioxide when the raw materials are mixed and kneaded, after molding, or after the coating layer is formed. This treatment may be performed, for example, by introducing a gas containing carbon dioxide into a kneader when the raw materials are mixed and kneaded, or by contacting the adsorbent 100 with a gas containing carbon dioxide after molding or after the coating layer is formed. The gas used may be a mixed gas containing carbon dioxide or carbon dioxide and other gases. Examples of other gases include nitrogen, oxygen, air, rare gases such as argon, and water (water vapor). The carbon dioxide concentration in the gas may also be set arbitrarily, and may be appropriately set within the range of, for example, 1% by volume or more and 100% by volume or less, 1% by volume or more and 50% by volume or less, or 1% by volume or more and 20% by volume or less. The temperature in this treatment may be, for example, 0°C or more and 80°C or less, or 0°C or more and 50°C or less, and is typically room temperature (25°C or thereabouts). By this treatment, all or a part of the compounds of alkali metals and alkaline earth metals contained in the porous carbide or added during the above-mentioned mixing and kneading are converted into carbonates or hydrogen carbonates.

[0057] An example of a source of the gas containing carbon dioxide is a cylinder or tank of the gas containing carbon dioxide. Alternatively, exhaust gas from a facility that emits a large amount of carbon dioxide (such as a chemical plant, a waste incineration facility, a thermal power plant, or various other factories) or purified carbon dioxide obtained by subjecting the exhaust gas to dust removal, desulfurization, denitrification, or the like may be used. If the facility that emits a large amount of carbon dioxide is close to the manufacturing site of the adsorbent 100, the facility functions as a source of the gas containing carbon dioxide, thereby reducing the cost of transporting carbon dioxide and preventing secondary emissions of carbon dioxide associated with the transportation.

[0058] 2-5. Drying (curing) Furthermore, as an optional step, the mixture after molding or the adsorbent 100 after the coating layer 104 is formed may be dried. The drying temperature and time are also appropriately selected depending on the amount of the mixture or the adsorbent 100 and the amount of water contained therein. For example, the drying temperature may be selected from the range of 30°C or more and less than 400°C, 50°C or more and less than 300°C, or 100°C or more and less than 300°C. The humidity during drying may be 20% or more and less than 95%, or 50% or more and less than 90%. The drying time may also be appropriately selected from the range of 1 minute or more and less than 1 week, 1 hour or more and less than 3 days, or 3 hours or more and less than 1 day. The atmosphere during drying may be, for example, air, nitrogen, a rare gas such as argon, or a mixture of these. The carbon dioxide treatment described above may also serve as a drying step. That is, the amount of water contained in the core 102 may be reduced by treating it with a gas containing carbon dioxide.

[0059] It should be noted that in the manufacture of the adsorbent 100 according to one embodiment of the present invention, it is not necessary to perform firing at a high temperature. In other words, it is not necessary to perform heating at a temperature (e.g., 400° C. or higher) required to carbonize the binder. This eliminates the need for the time and energy required for firing, and allows the adsorbent 100 to be provided at a lower cost.

[0060] As described above, in the manufacturing method of the adsorbent 100 according to one embodiment of the present invention, the core 102 containing the porous carbide, the binder, and iron is covered with the coating layer 104. Therefore, the physical strength is improved by the coating layer 104, and the adsorbent 100 can be prevented from collapsing in water. Furthermore, the ignition property of the porous carbide, which is a combustible material, is also significantly reduced, so that the adsorbent 100 can be handled as a highly safe non-hazardous material. Furthermore, as shown in the examples, even if the coating layer 104 is formed, the adsorbent 100 exhibits sufficient phosphate adsorption ability. Therefore, it can be said that the adsorbent 100 according to one embodiment of the present invention is an adsorbent that combines high phosphate adsorption ability and safety.

[0061] <Second embodiment> In this embodiment, a system that contributes to reducing carbon dioxide in the atmosphere via the adsorbent 100 described in the first embodiment will be described with reference to FIG.

[0062] As described in the first embodiment, in the manufacture of the adsorbent 100 according to one embodiment of the present invention, a porous carbonized material obtained from biomass can be used as one of the raw materials. In this case, the dry distillation gas obtained by carbonizing the biomass can be used as a combustible gas to generate electricity or produce hot water (FIG. 3, (1)). This means that the energy and by-products generated during the manufacture of the adsorbent 100 can be effectively utilized.

[0063] The resulting porous carbide is mixed and kneaded with iron powder and a binder to give the core 102 of the adsorbent 100, which is then coated with a coating layer 104 to obtain the adsorbent 100 (FIG. 3, (2)). The carbide carrying iron or iron compounds effectively adsorbs contaminants in water, particularly phosphorus-containing compounds such as phosphoric acid. Therefore, by placing this adsorbent 100 in bodies of water such as rivers, lakes, and oceans, water quality can be improved (FIG. 3, (3)).

[0064] Phosphate adsorbed to the adsorbent 100 is a typical component of nutrients that promotes the growth of various plants. Therefore, the adsorbent 100 with adsorbed phosphoric acid can be used as a fertilizer. For example, the adsorbent 100 that has been subjected to water quality improvement treatment is spread on farmland as is or after crushing and classification (FIG. 3, (4)). Alternatively, it may be spread after mixing with a fertilizer assistant such as calcium sulfate or other fertilizer components. The fertilizer components to be added include one or more selected from nitrogen, potassium, calcium, magnesium, manganese, silicic acid, and boron. Specific examples of materials include oil cake, flavored chicken droppings, fish meal, bone meal, rice bran, bat guano, pocassi fertilizer, wood ash, lime, and chemical fertilizer.

[0065] The sprayed adsorbent 100 gradually releases the adsorbed phosphoric acid, which is used for the growth of the plants. At this time, the plants use carbon dioxide in the atmosphere as a carbon source for photosynthesis and grow (Fig. 3, (5)). The plants are then used in various ways, such as as food or materials. After use, the plants can be used again as biomass to manufacture porous charcoal (Fig. 2, (6)).

[0066] In this way, by applying the embodiment of the present invention, a cycle is established, which includes the production of porous charcoal from biomass, the production of adsorbent 100, water quality improvement and fertilizer production, the growth of plants that use the fertilizer, and the regeneration of biomass. In this cycle, the carbon dioxide in the atmosphere fixed by the plants is used as a carrier for iron and iron compounds that exhibit phosphate adsorption function, and is stored in the ground in the form of carbon. Therefore, this cycle is a system that reduces and stores carbon dioxide in the atmosphere in the ground, and contributes to reducing carbon dioxide in the atmosphere. EXAMPLES

[0067] In this example, the preparation of an adsorbent 100 according to one embodiment of the present invention and the results of evaluating the adsorbent 100 will be described.

[0068] 1. Preparation of Adsorbent 1-1. Example 1 Irregularly shaped charcoal (waste charcoal from wood biomass gasification power generation) was used as the raw material porous charcoal. Iron powder with 24% by mass of iron particles having a particle size in the range of 300 μm to 600 μm, 56% by mass of iron particles having a particle size in the range of 75 to less than 300 μm, and 20% by mass of iron particles having a particle size in the range of 1 μm to less than 75 μm was added to 45 g of this charcoal and mixed with a spatula for 1 minute. 7 g of molasses (solid content 70%), calcined gypsum, and 40 mL of water were added to this mixture at room temperature and mixed to obtain a powder mixture.

[0069] Next, the obtained powder mixture was charged into a granulator and formed into a pellet shape having a diameter of 6 mm and a height of 9 mm, thereby obtaining the core 102 .

[0070] Thereafter, the obtained core 102 was placed in a pan-type granulator, and while rotating the core 102, an aqueous solution in which sodium silicate No. 3 was diluted to 75% with water in an amount of 200% by weight was sprayed onto the core 102. Thereafter, the core 102 was dried (cured) for 24 hours in air at 20°C to obtain the adsorbent 100.

[0071] 1-2. Examples 2 to 4 The adsorbent 100 of Examples 2 to 4 was produced in the same manner as in Example 1 by changing the type of binder, the material of the coating layer 104, the drying temperature and time, etc. Detailed conditions are as shown in Table 1. In Examples 2 and 3, carbon dioxide was used instead of argon, and carbonation was performed by drying (curing) under conditions of 80% humidity.

[0072] [Table 1]

[0073] 1-3.Comparative Example As a comparative example, an adsorbent was prepared in the same manner as in Example 1, except that the coating layer 104 was not formed.

[0074] 2. Evaluation 2-1. Phosphorus adsorption capacity and shape stability The amount of phosphoric acid adsorbed by the adsorbent 100 of the example was evaluated using a batch method. 0.1 g of any of the adsorbents of examples 1 to 4 was added to 50 mL of a 200 mg / L phosphoric acid solution, and the solution was horizontally shaken at 23°C and 100 rpm until an equilibrium concentration was reached, followed by filtration. The phosphorus concentration of the filtrate was quantified by molybdenum blue absorptiometry. The results are shown in Table 1. As shown in Table 1, it was confirmed that the adsorbents 100 of all examples exhibited the ability to adsorb phosphoric acid.

[0075] It was also confirmed that in all of the Examples, the adsorbents maintained almost their original shape in the phosphoric acid solution after the evaluation of the phosphate adsorption ability. On the other hand, the adsorbents of the Comparative Examples collapsed in water. From this, it can be understood that the adsorbent 100 having the structure of the core 102 / coating layer 104 is subject to low rate of erosion by water and exhibits high shape stability in water. 2-2. Small gas flame ignition test A small gas flame ignition test was conducted on the adsorbents obtained in Examples 1 to 4. Specifically, 1.5 g of the adsorbent was placed on a magnetic heat-resistant plate, and ignition was attempted using a gas burner. The length of the flame of the gas burner was about 70 mm, the contact area between the flame and the adsorbent was 1 to 2 cm2, the contact angle between the flame and the adsorbent was about 30°, and the contact time between the flame and the adsorbent was 10 seconds. This operation was repeated 10 times. As a result, it was confirmed that none of the adsorbents ignited.

[0076] These results show that the adsorbent 100 has both shape stability and non-ignition properties in water without impairing its phosphate adsorption ability due to the presence of the coating layer 104. Therefore, by applying one of the embodiments of the present invention, it is possible to provide an adsorbent that is highly effective in improving water quality over a long period of time and can be safely handled as a non-hazardous material.

[0077] The above-described embodiments of the present invention may be combined as appropriate as long as they are not mutually inconsistent. Any embodiment in which a person skilled in the art appropriately adds or deletes components or modifies the design based on each embodiment is also included in the scope of the present invention as long as it includes the gist of the present invention.

[0078] Even if there are other effects and advantages different from those brought about by the respective embodiments described above, those which are clear from the description in this specification or which can be easily predicted by a person skilled in the art are naturally understood to be brought about by the present invention. [Explanation of symbols]

[0079] 100: adsorbent, 102: core, 104: coating layer

Claims

1. a core comprising a porous carbide, a binder, and an iron powder; and A coating layer covering at least a portion of the core, The coating layer comprises an inorganic compound, the core further comprises a compound of a metal selected from alkali metals and alkaline earth metals; said compounds being selected from chlorides, oxides, hydroxides, sulfates, nitrates, carbonates, and bicarbonates of said metals; The content of the porous carbide is 20% by mass or more and 80% by mass or less, The content of the binder is 5% by mass or more and 50% by mass or less, The content of the iron powder is 5% by mass or more and 35% by mass or less. The content of the metal is 1% by mass or more and 10% by mass or less, An adsorbent having a pellet shape with a length to diameter ratio of 0.5 to 5, said diameter being 1 mm to 20 mm.

2. 10. The adsorbent of claim 1, wherein the coating layer comprises a material selected from sodium silicate, potassium silicate, silicon oxide, iron powder, gypsum, and cement.

3. The carbon content is 10% by mass or more and 80% by mass or less, The iron content is 5% by mass or more and 35% by mass or less, The adsorbent according to claim 1 , wherein the metal content is from 1% by mass to 30% by mass.

4. The adsorbent of claim 1 further comprising an iron compound.

5. 5. The adsorbent of claim 4, wherein the iron compound is selected from divalent and trivalent iron oxides and divalent and trivalent iron hydroxides.

6. 2. The adsorbent according to claim 1, wherein the binder is selected from molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified form thereof, pulp waste liquor, lignin sulfonate, carboxymethylcellulose, hydroxypropylmethylcellulose, sodium alginate, phenolic resin, tar pitch gypsum, cement, ground granulated blast furnace slag, fly ash, calcined gypsum, and sodium silicate.

7. mixing the porous carbide with a binder and iron powder to prepare a core; The core is granulated into a pellet shape having a length to diameter ratio of 0.5 to 5 and a diameter of 1 mm to 20 mm; forming a coating layer over at least a portion of the core; The coating layer comprises an inorganic compound, the core further comprises a compound of a metal selected from alkali metals and alkaline earth metals; said compounds being selected from chlorides, oxides, hydroxides, sulfates, nitrates, carbonates, and bicarbonates of said metals; The content of the porous carbide is 20% by mass or more and 80% by mass or less, The content of the binder is 5% by mass or more and 50% by mass or less, The content of the iron powder is 5% by mass or more and 35% by mass or less. The method for producing an adsorbent, wherein the metal content is 1% by mass or more and 10% by mass or less.

8. The method of claim 7 , wherein the coating layer comprises a material selected from sodium silicate, potassium silicate, silicon oxide, iron powder, gypsum, and cement.

9. 8. The method according to claim 7, wherein the binder is selected from the group consisting of molasses, blackstrap molasses, starch, dextrin, corn starch, rice bran, polyvinyl alcohol, a copolymer of vinyl acetate and ethylene or a saponified product thereof, pulp waste liquor, lignin sulfonate, carboxymethylcellulose, hydroxypropylmethylcellulose, sodium alginate, phenolic resin, tar pitch gypsum, cement, ground granulated blast furnace slag, fly ash, calcined gypsum, and sodium silicate.

Citation Information

Patent Citations

  • Oxygen absorbent

    JP1984052528A

  • Solid deoxidating agent and deoxidant

    JP2001314756A

  • Phosphorus recovering material, its producing method and its effectiveness as fertilizer

    JP2007075706A

  • Deoxidizer composition

    WO2017169015A1

  • Oxygen scavenger composition

    WO2021187130A1